Appreciation of biodiversity in Qur'anic account: an investigation on ecological maintenance - Shogar, Ibrahim (KOS, 2017)
Preservation of biodiversity is a major concern of the global community today. The continuous destruction of natural ecosystems is threatening the life on earth. The two major sources of the crisis, as identified by the available literature, are the need to satisfy the ever increasing human needs for development, and the climate change that follows. It seems to be a create paradox. Both, the religious contribution and scientific conclusions are necessary to deal with the matter. Although a considerable literature is already available on the topic, farther investigation is still necessary for preservation of biodiversity and maintenance of ecosystems. The central question that arises, in this context, would be about the nature of contribution that might be provided by Islamic teachings, especially the Qur`anic view on biological phenomenon, to deal with the ecological problems. The major objective of this paper is to examine this key question. The holy Qur`an is word of God that revealed, with instructions (awamir & nawahi), to guide man to the best choices. The natural biodiversity, on the other hand, is created by God with fixed laws to satisfy human needs and shift man’s attention, through systematic functions, to two forms of knowledge: (i) the practical knowledge of creatures for various purposes; and (ii) the theoretical knowledge that concluded from knowledge of creatures to recognize their Creator. To observe revealed guidance is a moral value and ethical obligation; while observation of natural laws in the created world is an epistemic value and scientific obligation. These are the two forms of knowledge that obligated to mankind to establish foundations of a meaningful life. Advancement in science and technology that based on moral values is, therefore, the core of development and key factor of progress in human society. The holy Qur`an appreciates the natural life and urges for protection of ecosystems and preservation of biodiversity for the above two purposes.